Flora e vegetação do sudoeste de Portugal continental - Neto, Carlos (2009)
The present paper presents the updated syntaxonomical typology of southwest mainland Portugal, complemented with the table of correspondence of each syntaxon with the NATURA 2000 habitats code (when applicable) as well as the floristic catalog of the studied area. All the syntaxa include chorological, synecological and floristic information. Regarding the lower level syntaxa (association and subassociation), its characteristic and differential taxa are cited. New syntaxa are accompanied by its typus relevé, chorological information, sinecology and reference to characteristic and differential taxa.